Circulating cell-free DNA methylation as biomarker for lung cancer detection: a systematic review and meta-analysis of diagnostic studies - Diana Inês Machado; Tiago Brito-Rocha; Sofia Salta; Teresa Monjardino; Rui Henrique; Carmen Jerónimo (Systematic Reviews)
Abstract Lung cancer (LC) is the most incident malignancy and a leading cause of cancer-related fatalities. The lack of dissemination of effective screening tools hinders early detection, resulting in late-stage diagnosis, mostly associated with high mortality. Gene-specific methylation alterations detected in plasma or serum circulation cell-free DNA (ccfDNA) have been investigated as a possible screening tool. Thus, the main aim of this systematic review and meta-analysis was to critically assess published data on the use of ccfDNA methylation-based biomarkers for detection of LC. PubMed, including MEDLINE and Scopus databases, were systematically searched for eligible articles evaluating the diagnostic performance of ccfDNA methylation alterations in that setting. A bivariate random-effect model was employed to calculate pool estimated sensitivity and specificity. Accuracy subgroup analyses, according to histological subtype, stage, and smoker status were carried out. A total of 1961 articles were retrieved, of which 44 met inclusion criteria. The meta-analysis generated a pooled sensitivity of 54% (CI 95% 48–60%) and a pooled specificity of 86% (CI 95% 83–87%) for LC detection. The most frequently tested host-genome methylation markers were RASSF1 A, APC, SHOX2, SOX17, and HOXA9. Overall, methylation analysis of ccfDNA detects LC with high specificity but modest sensitivity. Further research is required to improve diagnostic performance, establish methodological standards and determine whether this might complement existing screening strategies to increase effectiveness. Systematic review registration PROSPERO CRD42023408964.